AC conductivity, electric modulus analysis and electrical conduction mechanism of RbFeP2O7 ceramic compound. Issue 12 (September 2016) - Nasri, S.; Oueslati, A.; Chaabane, I.; Gargouri, M.
Abstract: In this work, the diphosphate compound, RbFeP2 O7, was prepared by the conventional solid-state reaction. The X-ray diffraction pattern revealed that the sample presents a single phase, that crystallizes in the monoclinic structure with a P21 /C space group. Impedance analysis was performed using the equivalent circuit model, and, it indicated the presence of intra- and inter-granular contribution. Furthermore, the electrical conductivity, the dielectric properties and the relaxation behavior of this material were studied in detail using the impedance spectroscopy technique, in a frequency ranging from 200 Hz to 5 MHz at several temperatures. The temperature dependency of frequency exponent 's' shows that the correlated barrier-hopping model (CBH) is the most responsible mechanism for AC conduction in the investigated compound. In terms of CBH model, the values of maximum barrier s height, the hopping distance and the density of localized states are determined and discussed. A correlation between electrical and structural properties was also discussed.